Role of Signaling Molecules in Mitochondrial Stress Response - Hill, Shauna; Sataranatarajan, Kavithalakshmi; Van Remmen, Holly (Frontiers in Genetics, 2018)
Mitochondria are established essential regulators of cellular function and metabolism. Mitochondria regulate redox homeostasis, maintain energy (ATP) production through oxidative phosphorylation, buffer calcium levels, and control cell death through apoptosis. In addition to these critical cell functions, recent evidence supports a signaling role for mitochondria. For example, studies over the past few years have established that peptides released from the mitochondria mediate stress responses such as the mitochondrial unfolded protein response (UPRMT) through signaling to the nucleus. Mitochondrial damage or danger associated molecular patterns (DAMPs) provide a link between mitochondria, inflammation and inflammatory disease processes. Additionally, a new class of peptides generated by the mitochondria affords protection against age-related diseases in mammals. In this short review, we highlight the role of mitochondrial signaling and regulation of cellular activities through the mitochondrial UPRMT that signals to the nucleus to affect homeostatic responses, DAMPs, and mitochondrial derived peptides.